ANALISIS FUNDAMENTAL YANG MEMPENGARUHI HARGA SAHAM PERUSAHAAN PERTAMBANGAN DAN INDUSTRI DASAR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2009-2011 - Mirna Tyas Paramita; Akhmad Sayudi (JWM (JURNAL WAWASAN MANAJEMEN), 2017)
The purpose of this study was to analyze the effects of the Price Earning Ratio (PER), Return on Equity (ROE), Debt Total Asset (DTA), Current Ratio (CR) and Price to Book Value (PBV) on the stock price of mining industry and basic industry registered at the Indonesian Stock Exchangw in 2009-2011. The sampling method used was purposive sampling by selecting samples based on certain criteria. The objects which became the samples were 37 companies from 77 companies in the period of 2009-2011 so that the number of the companies were 111. The research used linear multiple regression analysis. The result of this research showed that the Price Earning Ratio (PER), Return on Equity (ROE), Debt Total Asset (DTA), Current Ratio (CR) and Price to Book Value (PBV) simultaneously affected the stock price of mining industry and basic industry for the period 2009-2011. The result of this research partially showed that Return on Equity (ROE),Current Ratio (CR) and Price to Book Value (PBV) affected the stock price.